Quantity FOOD PRODUCTION, PLANNING, AND MANAGEMENT - Knight, John Barton, 1950- (John Wiley & Sons, 2000)
A major revision of a classic text-how to be an effective foodservice manager. When it comes to handling the demands of the foodservice industry, there is no single approach. Quantity Food Production, Planning, and Management goes beyond the mere teaching of technical skills to address the multitude of situations and challenges facing operators today. Now in a new edition, this classic hospitality management text continues to set the standard for planning production, executing culinary technique, and understanding food and beverage management